Postpartum relapses increase the risk of disability progression in multiple sclerosis: the role of disease modifying drugs. Issue 8 (8th January 2014) - Portaccio, Emilio; Ghezzi, Angelo; Hakiki, Bahia; Sturchio, Andrea; Martinelli, Vittorio; Moiola, Lucia; Patti, Francesco; Mancardi, Gian Luigi; Solaro, Claudio; Tola, Maria Rosaria; Pozzilli, Carlo; De Giglio, Laura; et al.
Abstract : Objective: To assess relapses, disability progression and the role of disease modifying drugs (DMDs) in the year after delivery in women with multiple sclerosis (MS). Methods: We prospectively followed-up pregnancies occurring between 2002 and 2008 in women with MS, recruited from 21 Italian MS centres. The risk of relapses and disability progression in the year after delivery was assessed using time-dependent Cox regression analysis. Results: 350 out of 423 pregnancies were assessed (pregnancies not resulting in live birth and with a postpartum follow-up period shorter than 1 year were excluded from the analysis). 148 patients (42.3%) had at least one relapse in the year after delivery. An Expanded Disability Status Scale (EDSS) score at conception ≥2.0 (HR=1.4; 95% CI 1.1 to 2.0; p=0.046) and a higher number of relapses before (HR=1.5; 95% CI 1.2 to 1.8; p<0.001) and during pregnancy (HR=2.3; 95% CI 1.6 to 3.4; p<0.001) were related to a higher risk of postpartum relapses. On the contrary, early DMD resumption after delivery marginally reduced the risk of postpartum relapses (HR=0.7, 95% CI 0.4 to 1.0; p=0.079). Moreover, 44/338 women progressed by at least one point on the EDSS. Disability progression was associated with a higher number of relapses before (HR=1.4, 95% CI 1.1 to 1.9; p=0.047) and after delivery (HR=2.7, 95% CI 1.4 to 5.2; p=0.002). Conclusions: Our findings show an increased risk of postpartum relapses and disability accrual in women with higher disease activity before and during pregnancy. Since it may reduce the risk of postpartum relapses, early DMD resumption should be encouraged, particularly in patients with more active disease.